Dampak Penerapan Elfan Bookless Library System di Dinas Perpustakaan dan Kearsipan Daerah Kabupaten Sinjai - Salma, Salma; Congge, Umar (Journal of Government Insight, 2023)
Digital libraries are one of the government's innovative products in an effort to increase interest in literacy and provide a place of reference for the community which is expected to function better. This digital library has been implemented in several regions in Indonesia, one of which is in Sinjai Regency. the policy of implementing digital libraries in Sinjai Regency began to be implemented in 2019. This article uses qualitative research with a descriptive approach. The data obtained is then selected, presented and analyzed using the content analysis method. The results of the study show thatElfan Bookless Library System contains approximately 5000 books that can be accessed by users. The Sinjai Regional Library and Archives Service provides services to visitors by using a QR Code that can be scanned at the Sinjai Regional Library and Archives Service. In addition, the free internet network also makes it easy for visitors to access these services. However, the majority of visitors are not aware of any information on these digital library services which is presented side by side with POCADI (Digital Reading Corner).